Biotechnological Potential of Yarrowia lipolytica Grown under Thiamine Limitation - Maria N. Chiglintseva; Alsu I. Yusupova; Natalia G. Vinokurova; Valentina Ya. Lysanskaya; Igor G. Morgunov; Svetlana V. Kamzolova (Food Technology and Biotechnology, 2012)
During the cultivation of a thiamine-auxotrophic yeast strain Yarrowia lipolytica VKM Y-2412 on ethanol, the growth limitation by thiamine leads to the production of α-ketoglutaric acid. The α-ketoglutaric acid synthesis has been studied in dependence on pH, oxygen supply and ethanol, zinc and iron concentrations. Under optimal conditions, Y. lipolytica produced 88.7 g/L of α-ketoglutaric acid. The culture broth containing α-ketoglutaric acid was subjected to chemical treatment with hydrogen peroxide, which led to the formation of succinic acid in significant quantities (71.7 g/L). Further direct esterification of succinic acid with excess absolute ethanol yielded diethyl succinate. Biomass of Y. lipolytica, a superproducer of α-ketoglutaric acid, was characterized by a high content of protein and essential amino acids, free amino acids, and unusually large amount of γ-aminobutyric acid. The unique amino acid composition of the producer makes it possible to use this biomass as a component of parenteral nutrition mixtures and as a basis for neuroleptics.